Introduction to C++ programming - Malik, D. S. (Boston, MA : Course Technology, Cengage Learning, 2009)
'Brand new from best-selling author D.S. Malik, PROGRAMMING WITH C++: BRIEF EDITION provides readers with a succinct introduction to the C++ language supported by the rich pedagogy that has made his past offerings so successful. This text addresses the key issues that impede student learning, including how data in a variable is manipulated and how actual and formal parameters relate. Once students understand these fundamental concepts, they readily assimilate advanced topics. Each chapter offers extensive examples and diagrams as well as complete Programming Examples.'--Book cover.
An overview of computers and programming languages -- Basic elements of C++ -- Input/output -- Control structures I (selection) -- Control structures II (repetition) -- User-defined functions -- Arrays -- Classes and data abstraction -- Namespaces, the'class string,' and user-defined simple data types -- Pointers -- Applications of arrays (searching and sorting) and the'class vector' -- Recursion.
Includes index.
Keywords: C++ (Computer program language